Interpenetration and Mutual Influence of Terminological, General-Purpose, and Colloquial Vocabulary (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article examines the phenomenon of interpenetration and mutual influence between terminological, general-purpose (neutral), and colloquial vocabulary in contemporary language systems. As societies evolve and scientific, technological, and cultural changes accelerate, the boundaries between specialized and everyday language become increasingly fluid. This dynamic interaction contributes to linguistic innovation, borrowing, semantic shifts, and stylistic hybridity. The article explores theoretical frameworks, provides practical examples from different languages, and analyzes implications for lexicography, language teaching, and cross-cultural communication.